Mechanical and thermal properties of polypropylene/montmorillonite nanocomposites using stearic acid as both an interface and a clay surface modifier. Issue 1 (15th August 2013) - Gonzalez, Lucas; Lafleur, Pierre; Lozano, Tomas; Morales, Ana B.; Garcia, Ricardo; Angeles, Marisela; Rodriguez, Francisco; Sanchez, Saul
<x xml:space="preserve">Abstract</x> The effects of stearic acid treatment on the crystallization, morphology, thermal, and mechanical properties of polypropylene (PP)/montmorillonite (Mm) nanocomposites were investigated. Stearic acid was used as a new surface modifier for Mm, and also small amounts of this acid were used as a new interface modifier. Nanocomposites containing 1.5, 2.5, 5, and 10% in weight of the unmodified and modified Mm were prepared by melt blending. The tensile and impact properties of nanocomposites were evaluated. Wide‐angle X‐ray diffraction was used to study both the generated PP β crystals and the dispersion state of the nanocomposites. Differential scanning calorimeter was used to detect the melting and crystallization behavior of the samples. The toughness of some nanocomposites was higher than the pure PP. β phase of PP was observed with the addition of Mm. Stearic acid favored the dispersion of the nanocomposites when used as interface modifier. Nanocomposites with better dispersion exhibited crystallization temperatures similar to pure PP. POLYM. COMPOS., 35:1–9, 2014. © 2013 Society of Plastics Engineers